A Study on the local geotechnical status of alluviums lie on the bedrock of Tabriz city - Javdani, Ali; Yusefzadeh-Fard, Mikael (Ciência e Natura, 2015)
Tabriz is one of cities in Iran that has faced several earthquakes because it is located on a fault. Different parameters are involved related toseismic hazards of one particular region, that investing each of them is essential. One of the effective factors that has been recognized according todifferent earthquake experiences worldwide, is the local and geotechnical status of alluviums lie on the bedrock. In this study in order to acquirethe earthquake acceleration in the region seismic bedrock, the “PSHA” probabilistic procedure has been applied. In this regard, firstly seismicparameters of the region have been acquired and then considering all the faults of the region and modeling the seismic sources and by means of“Seisrisk” software, the maximum acceleration of the bedrock (PGA) for an earthquake with return period of 475 years in the urban range hasbeen resulted which have been presented as level curve maps of maximum acceleration of bed rock. Afterwards by means of Geotechnical datacollected from exploratory bore holes excavated in the region and other sources, finally 51 representative seismic Geotechnic profiles has beenprepared. in order to execute the alluvium response analyze, region bedrock seismic movement estimation is needed. Thus considering all factors,8 appropriate entrance accelerograms opted and maximum acceleration of these accelerograms tantamounted to maximum acceleration of seismicbedrock in range of each section and each representative section for these 8 accelerograms has been analaysed. According to almost horizontalstatus of alluvium layers of the region, one dimensional dynamic analyze has been applied in order to calculate the dynamic response of soillayers. In addition the linear equivalent analysis procedure in mediocre strain range and hypothesis of no failure due to earthquake in alluvium,has made the use of EERA software possible in this study. The results of analysis of alluvium response for regions in the city which geotechnicalspecifications of alluvium layers had been collected, has been presented as maximum acceleration distribution and response acceleration spectrummaps on the ground for entrance movements and alluvium normal period distribution map. Alluvium response analyze results shows thatacceleration on ground level will have amounts between 0.55g up to 0.75g for an earthquake with returning period of 475 years . Also in studyrange, regions with alluvium natural period more than 0.45 sec and less than 0.3 sec exist.